Massive Submandibular Sialolith: Complete Radiographic Registration and Biochemical Analysis through X-Ray Diffraction - Ademir Franco; Mayara Jessica de Carvalho Mattos; Francine Ferrari; José Manoel dos Reis Neto; Luiz Carlos Carta Gambus; Paulo Henrique Couto Souza; Soraya de Azambuja Berti-Couto (Case Reports in Surgery)
Sialolithiasis is a pathologic condition that affects 60 million people per year, which is caused by the presence of calcified structures, named sialoliths, inside the salivary glands and their salivary ducts. Despite the large incidence of sialolithiasis, its etiology is still unknown. In the present case report, a 47-year-old female patient, presenting with local pain and hampered mouth opening, underwent a surgical approach for the removal of a 20 mm sialolith, which was further analyzed through X-ray diffraction. In parallel, a radiographic registration of 8 years, covering all the period for sialolith formation, is presented along the case report.